Spatial neglect in a patient with logopenic progressive aphasia. Issue 1 (2nd January 2016) - Zilli, Eduardo M.; Heilman, Kenneth M.
Abstract : Spatial neglect and extinction are induced by posterior superior temporal and inferior parietal dysfunction. In patients with logopenic progressive aphasia (LPA) these structures are often degenerated, but there are no reports of these disorders being associated. A 53-year-old man with the signs of LPA revealed right-sided spatial neglect on line bisection and drawing tests as well as multimodal extinction. MRI showed left hemispheric posterior temporoparietal atrophy. Since injury to the core structures for these aphasic and attentional syndromes overlaps, patients with LPA should be screened for spatial neglect and extinction.